Identification of a Sub-Clinical Salmonella spp. Infection in a Dairy Cow Using a Commercially Available Stool Storage Kit - Alice Nishigaki; Renato Previdelli; James L. Alexander; Sharmili Balarajah; Lauren Roberts; Julian R. Marchesi (Animals, 2023)
Stool sampling is a useful tool for diagnosing gastrointestinal disease in veterinary medicine. The sub-clinical disease burden of Salmonella spp. in cattle can become significant for farmers. However, current methods of faecal sampling in a rural setting for diagnosis are not consistently sufficient for the preservation of Salmonella spp. in faeces. This study evaluated the use of a commercial stool storage kit for bacterial preservation in cow faecal samples compared to unpreserved stools placed into refrigeration at different time-points. A stool sample was collected per-rectum from one apparently healthy Holstein–Freisen cow. The sample was weighed and aliquoted into two sterile Falcon tubes and into two commercial kit tubes. The aliquots were then placed into refrigeration at 4 °C at 0, 24, and 96 h after processing. One commercial kit tube was not aliquoted and remained at ambient temperature. After 2 weeks, DNA was extracted from the samples and analysed using endpoint PCR, revealing a sub-clinical infection with Salmonella spp. The bacterium was best preserved when the stool was stored in the commercial kit at ambient temperature and re-homogenised immediately prior to DNA extraction. The unpreserved stool did not maintain obvious levels of Salmonella spp. after 24 h at ambient temperature. This commercial kit should be considered for use in the diagnosis of salmonellosis in cattle.